Evidence Based Insights on Homeopathic Management in Tonsillitis : inflammatory condition (Homoeopathy for All, 2025)
Tonsillitis is a common  inflammatory condition of the  palatine tonsils, primarily affecting  children and adolescents. It is  predominantly triggered by viral  or bacterial acute throat infections  (ATIs) and typically presents with  sore throat, fever, and tonsillar  hypertrophy. Although diagnosis  is mostly clinical, differentiating  between viral and bacterial causes  can often be challenging. Recurrent  tonsillitis is defined as the repeated  occurrence of ATIs, interspersed  with asymptomatic intervals or  periods with minimal symptoms.  This condition has far-reaching  implications, including frequent  school or work absenteeism,  sleep disturbances, generalized  discomfort, and increased healthcare  visits all of which contribute to  substantial socio-economic burden  and diminished quality of life for  patients and their families.
Keywords: inflammatory condition; sleep disturbances; intervention; asymptomatic intervals